2017
DOI: 10.15407/mfint.39.09.1281
|View full text |Cite
|
Sign up to set email alerts
|

On the Issue of the Nature of Tetragonality of a Martensite

Abstract: Рассмотрена тетрагональность мартенсита в углеродистых сталях; прове-дён анализ имеющихся литературных данных. Введено понятие предель-ной или идеальной тетрагональности и вычислена её величина. Показано, что реальная тетрагональность, определяемая рентгенографически, есть некоторая усреднённая по всему объёму мартенситной фазы величина. Предложено объяснение так называемого кубического мартенсита, а также «нормальной» и «аномально низкой» тетрагональности в сталях.Ключевые слова: углеродистая сталь, мартенсит… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…It is seen that earlier data was available only for martensite of  0.6 wt.% C [6,15,22] due to the techniques limitations, whereas more recent one also covers 0.128-0.6 wt. % C range [12,25]. It should be also noted that data from Ref.…”
Section: Dependence Of Martensite Lattice Parameters On C Concentratimentioning
confidence: 95%
See 2 more Smart Citations
“…It is seen that earlier data was available only for martensite of  0.6 wt.% C [6,15,22] due to the techniques limitations, whereas more recent one also covers 0.128-0.6 wt. % C range [12,25]. It should be also noted that data from Ref.…”
Section: Dependence Of Martensite Lattice Parameters On C Concentratimentioning
confidence: 95%
“…In order to estimate this increase, the value of сγ could be extrapolated using Eq. 5 for a such hypothetical C concentration in which one C atom is located at each one of four cube edges [25,26]. Calculations showed that in this case there are two Fe atoms and one C atom per bct unit cell; three atoms in total.…”
Section: Distortion Of Bcc Lattice In Fe Due To Interstitial C Atomsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic amount of the martensite arising by the isothermal kinetics appears during first 20-25 minutes. Using these alloys, it was shown that under change of cooling velocity or state of the parent phase by ageing or deformation in the same CuSnGa alloy it can observe different kinetics of MT in different sequences: isothermal, isothermal  athermal, athermal  isothermal [7].…”
Section: Types Of the Martensitic Transformationsmentioning
confidence: 99%
“…C, may change the body centred cubic structure of iron (Fe α ) to the tetragonal structure. Only recently some works have appeared in which a new approach proposed for describing the crystal structure of the martensite in carbon steels [5,6].…”
Section: Introductionmentioning
confidence: 99%